The Influence of Self-Regulated Learning on Students’ Creative Thinking Skills - Suciati, Nela (Papanda Publisher, 2023)
This study investigates the influence of self-regulated learning (SRL) on students’ mathematical creative thinking. Grounded in correlational quantitative design, the research involved 120 ninth-grade students from a junior high school in West Java, Indonesia. Data were collected using a Self-Regulated Learning Questionnaire (SRLQ) and a Mathematical Creative Thinking Test (MCTT), both validated for reliability and content. Descriptive and inferential analyses revealed a significant and positive correlation (r = .682, p < .001) between SRL and creative thinking, supported by a regression model explaining 46.5% of the variance in creative thinking scores. Further comparison showed that students with high SRL levels significantly outperformed those with moderate and low SRL levels in creative mathematical tasks. These findings confirm that planning, monitoring, and reflecting—core SRL processes—contribute meaningfully to students' ability to generate original, flexible, and elaborative mathematical ideas. The study underscores the importance of integrating SRL strategies into mathematics instruction to enhance not only academic achievement but also creativity and independence in problem-solving. Educational implications include the development of pedagogical interventions such as metacognitive prompts, goal-setting routines, and reflective activities that cultivate SRL behaviors and foster creative engagemen